The foreigners´ temporary stay centres as the new model of migration control: current situation, legal (de)regulation and mechanisms of control and guarantee of rights - Barbero, Iker (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2021)
In recent years, due to the increase of rescues and coastal arrivals of migrants there has been a change in the containment model. If previously it were the Foreigners´ Detention Centres (or CIE) or the Immigrants´ Temporary Stay Centres (or CETI) the ordinary devices for managing arrivals and referral to other immigration procedures, at present, following the humanitarian-managerial logic of border control, the so-called Foreigners´ Temporary Stay Centres have been created de facto. These are fenced buildings or seals in port areas where people are kept for a maximum of 72 hours to proceed to their police proceedings. This article will argue that the absence of a legal regulation of these centers, in addition to adding legal insecurity to the actions of public administration personnel, makes it difficult to recognize fundamental rights of the people detained and omits control mechanisms essential in any democratic society.
Keywords: Foreigners´ Temporary Stay Centres; migration control; borders; fundamental rights; guarantee mechanisms